Counseling on Adolescent Reproductive Health (KRR) & Sadari Screening for Adolescents at SMAN 6 Gowa - M, Azrida; Thamrin, Halida; Karuniawati, Nia (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2020)
Adolescent Reproductive Health (RH) is something that must be known and understood by families and communities, especially adolescents. The problem is that adolescents are always faced with risks related to their reproduction. These risks include early and unwanted pregnancy, and abortion. Adolescents need to know about KRR (Adolescent Reproductive Health), among others for adolescent girls such as reproductive organs, menstruation, anemia and reproductive health, circumcision or circumcision in women and virginity. Health education that adolescents need to know includes reproductive health, breast self-examination, anemia and menstruation. From the results of interviews with several female students at the pesantren, female students have never received material or counseling on reproductive health. Based on these problems, it is very important for schoolgirls/adolescents to know, so that in the future there will be no more problems related to ignorance about Adolescent Reproductive Health.